An Overview of the α4β1 Integrin and the Potential Therapeutic Role of its Antagonists - Ferreira, Elenilze F.B.; Silva, Luciane B.; Cruz, Josiane V.; Araújo, Pedro H.F.; Kimani, Njogu M.; Leite, Franco H.A.; Campos, Joaquín M.; Santos, Cleydson B.R. (Current Medicinal Chemistry, 2021)
This article presents a simplified view of integrins with emphasis on the α4 (α4β1/VLA-4) integrin. Integrins are heterodimeric proteins expressed on the cell surface of leukocytes that participate in a wide variety of functions, such as survival, growth, differentiation, migration, inflammatory responses, tumour invasion, among others. When the extracellular matrix is degraded or deformed, cells are forced to undergo responsive changes that influence remodelling during physiological and pathological events. Integrins recognize these changes and trigger a series of cellular responses, forming a physical connection between the interior and the outside of the cell. The communication of integrins through the plasma membrane occurs in both directions, from the extracellular to the intracellular (outside-in) and from the intracellular to the extracellular (inside-out). Integrins are valid targets for antibodies and small-molecule antagonists. One example is the monoclonal antibody natalizumab, marketed under the name of TYSABRI®, used in the treatment of recurrent multiple sclerosis, which inhibits the adhesion of α4 integrin to its counter-receptor. α4β1 Integrin antagonists are summarized here, and their utility as therapeutics are also discussed.
Keywords: α4β1 integrin antagonists